2022
DOI: 10.7759/cureus.21673
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Primary Hyperoxaluria Type 1 Treated With Lumasiran in Twin Males

Abstract: Primary hyperoxaluria type 1 (PH1) is a rare genetic disease that results in oxalate overproduction leading to nephrolithiasis (NL), nephrocalcinosis (NC), kidney failure, and systemic oxalosis. Infantile PH1 is its most severe form, and it may require intensive hemodialysis followed by a liver-kidney transplant. Lumasiran is an RNA interference (RNAi) therapeutic agent that reduces hepatic oxalate production, which has been recently approved for the treatment of PH1. In this report, we present a case of twin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Lumasiran has shown promising clinical benefits in PH1 with sustained lowering of oxalate levels, acceptable safety, and encouraging results on clinical outcomes in clinical trials 28−31 and also benefits for management of PH1 in small infants 32 and twins 33 in the postmarketing studies.…”
Section: Acs Pharmacology and Translational Sciencementioning
confidence: 99%
“…Lumasiran has shown promising clinical benefits in PH1 with sustained lowering of oxalate levels, acceptable safety, and encouraging results on clinical outcomes in clinical trials 28−31 and also benefits for management of PH1 in small infants 32 and twins 33 in the postmarketing studies.…”
Section: Acs Pharmacology and Translational Sciencementioning
confidence: 99%
“…So far, experiences with Oxlumo ® treatment (outside long-term studies from the company itself) have been reported only in ten PH1 cases, both children (n = 7) [85][86][87][88] and adults (n = 3) [89-91] (Table 3) with the time under treatment reported as from 1 to 18 months. Good tolerance, reduced urinary oxalate/creatinine ratio, and stability (or even slight improvement) of renal function were reported only in the children treated.…”
Section: Substrate Reduction Therapies: the Expensive Approachmentioning
confidence: 99%
“…Glycolate not measured >5 months Fourth dose injected 3 months after third dose + B6 + citrate + hyperhydration Slight elevation of GGT and alkaline phosphatase. Developed non-anion gap metabolic acidosis (HCO 3 - 14 mmol/L and anion gap 8mmol/L) after HD discontinuation due to elevated glycolate Sodium bicarbonate resolved the metabolic acidosis 2 [ 87 ] Male Twin A 11 months old (p.Gly161Cys p.Gly170Arg) Passed stones at 6 weeks old. Kidney stone (100% CaOx) at 9 months old, bilateral UL and bilateral double-J stent.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of lumasiran in the treatment of the infantile form of PH1 still needs to be completely clarified and widely evaluated, however, there are some case reports in the literature that show evidence of lumasiran’s efficacy in improving clinical manifestations and quality of life in infantile forms. 56 …”
Section: Lumasiran: Current Clinical Evidencementioning
confidence: 99%